2021
DOI: 10.1186/s42523-020-00068-y
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of landscape and captivity in the gut microbiota of Southern Hairy-nosed Wombats (Lasiorhinus latifrons)

Abstract: Background Herbivorous mammals co-opt microbes to derive energy and nutrients from diets that are recalcitrant to host enzymes. Recent research has found that captive management—an important conservation tool for many species—can alter the gut microbiota of mammals. Such changes could negatively impact the ability of herbivorous mammals to derive energy from their native diets, and ultimately reduce host fitness. To date, nothing is known of how captivity influences the gut microbiota of the So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…Many studies that measured microbial diversity report decreased gut richness or diversity in individuals in captivity compared to others in the wild [e.g. 22 , 35 , 36 ]. However, some studies have reported no difference in microbial diversity between the two environments [e.g.…”
Section: Review Of Current Literature On the Captive Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies that measured microbial diversity report decreased gut richness or diversity in individuals in captivity compared to others in the wild [e.g. 22 , 35 , 36 ]. However, some studies have reported no difference in microbial diversity between the two environments [e.g.…”
Section: Review Of Current Literature On the Captive Microbiomementioning
confidence: 99%
“…There are alternative interpretations of microbial differences between wild and captive animals that do not presume the captive microbiome is less favorable [e.g. 35 , 86 88 ] or potentially detrimental [ 1 ]; these are important to consider in the absence of species-specific experimental evidence. First, microbiomes may have changed to match the new captive environment in a beneficial manner [ 89 ].…”
Section: Review Of Current Literature On the Captive Microbiomementioning
confidence: 99%
“…This suggests that seeking to understand microbial functions at the putative primary site of fermentation through faecal samples may not be feasible. This is not to say that faecal samples are not useful, as previous gut microbiome research on captive [22] and wild wombats [23,24] have yielded insights into wombat digestion and ecology. Eisenhofer et al used faecal samples from both captive and wild SHNWs to show that captivity has a large in uence on the faecal microbiota of SHNWs.…”
Section: Discussionmentioning
confidence: 99%
“…Eisenhofer et al used faecal samples from both captive and wild SHNWs to show that captivity has a large in uence on the faecal microbiota of SHNWs. They were also able to identify population-speci c microbial signatures and found a correlation between habitat type (degraded vs. intact) and faecal microbiota composition in SHNWs [23]. Shiffman et al used shotgun metagenomic sequencing on faecal samples collected from a captive SHNW, and found numerous microbial genes involved in plant degradation and urea recycling [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation